When Agile Means Staying: A Moderated Mediated Model. Issue 1 (2nd January 2022) - Setor, Tenace Kwaku; Joseph, Damien
ABSTRACT: The design of software development methods focuses on improving task processes, including accommodating changing user requirements and accelerating product delivery. However, there is limited research on how the use of different software development methods impacts IT professionals' perceptions of organizational mobility. Drawing on concepts from the agile development literature and job characteristics theory, we formulate a moderated mediation model explicating the mechanism and the condition under which agile development use exerts an influence on IT professionals' intention to stay with their current employer. Specifically, we examine job satisfaction as mediating the effect of using agile development on the intention to stay as well as how the strength of the mediated relationship differs across firms. We test our hypotheses using a sample of 32, 389 software developers. We find that job satisfaction fully mediates the effect of using agile development on the intention to stay. The strength of the mediation effect is significantly different for large and small firms.